H3K4 monomethylation dictates nucleosome dynamics and chromatin remodeling at stress-responsive genes. Issue 10 (26th March 2015) - Nadal-Ribelles, Mariona; Mas, Glòria; Millán-Zambrano, Gonzalo; Solé, Carme; Ammerer, Gustav; Chávez, Sebastián; Posas, Francesc; de Nadal, Eulàlia
Abstract: Chromatin remodeling is essential for proper adaptation to extracellular stimuli. The p38-related Hog1 SAPK is an important regulator of transcription that mediates chromatin remodeling upon stress. Hog1 targets the RSC chromatin remodeling complex to stress-responsive genes and rsc deficient cells display reduced induction of gene expression. Here we show that the absence of H3K4 methylation, either achieved by deletion of the SET1 methyltransferase or by amino acid substitution of H3K4, bypasses the requirement of RSC for stress-responsive gene expression. Monomethylation of H3K4 is specifically inhibiting RSC-independent chromatin remodeling and thus, it prevents osmostress-induced gene expression. The absence of H3K4 monomethylation permits that the association of alternative remodelers with stress-responsive genes and the Swr1 complex (SWR-C) is instrumental in the induction of gene expression upon stress. Accordingly, the absence of SWR-C or histone H2A.Z results in compromised chromatin remodeling and impaired gene expression in the absence of RSC and H3K4 methylation. These results indicate that expression of stress-responsive genes is controlled by two remodeling mechanisms: RSC in the presence of monomethylated H3K4, and SWR-C in the absence of H3K4 monomethylation. Our findings point to a novel role for H3K4 monomethylation in dictating the specificity of chromatin remodeling, adding an extra layer of regulation to the transcriptional stress response.